THE ESTABLISHMENT AND STAGES OF DEVELOPMENT OF NATIONAL DANCE SCHOOLS - Usmanova Gulasal Normuhammad qizi; Muhamedova Ugiloy Nizamovna; Makhmudova Malakhat Makhmudovna; Saitova Erkinoy Yakubovna; Yunusova Dilbar Mukhamedovna (Utilitas Mathematica, 2025)
This article presents a comparative analysis of scientific concepts aimed at studying the theoretical foundations and functions of Uzbek dance art. The theoretical ideas about the Uzbek dance art are presented on the basis of the set of scientific and theoretical views, system and their analysis regarding the influence of the traditional culture of the people on the national dance art. The researches of M. Rakhmonov, L. Avdeeva, R. Karimova and other scientists who researched the scientific basis of the introduction of the concept of "Uzbek dance" into science were summarized and theoretical conclusions were drawn.